Formation and stability of aerobic granular sludge in sewage treatment under low loading conditions / Nik Azimatolakma Awang - Nik Azimatolakma , Awang (2016)
The increasing pollution loads and types of pollutants constituents in sewage treatment plant (STPs) as compared to the original design requirement urge for a demand in upgrading of the old STPs. Land acquisition will become a major issue in upgrading the new STPs since conventional biological STPs requires a large footprint for the installation of reactors that accommodate different conversions and sludge stabilisation process. Aerobic granular sludge (AGS) technology offers a possibility in designing a compact STPs based on simultaneous organics and nutrient removal and settling process in a sequencing batch reactor (SBR). The research trend on AGS has been integrated from factors affecting the formation process and chemical characteristic towards the stability for a long term operation. Thus, this study is aimed to determine the formation and stability of AGS system in achieving stable conditions and after being tested with a series of constrained conditions will be a critical factor to highlight the environmental biotechnology novelty of AGS. In this research, a series of AGS Batches were developed in SBRs with different height/diameter (H/D) ratios at a similar working volume of 4.5 L and an aeration rate of 4 L/min. The performance of each Batch was assessed based on the biomass production, effluent quality and AGS characteristics, with the determination to correlate the operational conditions with AGS formation and stability. The results are divided into 5 major sections: 1) the effects of low organic loading rate (OLR), 2) the effects of differences in reactor H/D ratio, 3) the increase of formation and stability of AGS developed in a low reactor H/D ratio by adding divided draft tubes, 4) the reformation process of long term stored AGS and 5) the biokinetics parameters. First, AGS (Control Batch) was successfully attained after 55 days of a formation period although the applied OLR was exceptionally low, which were in range of 0.2 and 0.48 kg COD/m3 d. Second, although the periods to attain AGS (Batch1) in high H/D ratio reactor was shorter, AGS (Batch2) produced in a low H/D ratio reactor appeared to be more resistant towards fluctuated and low OLR by providing a short settling distance for biomass in facing the unfavorable circumstances. Third, the uses of divided draft tubes proved to be beneficial in shortening the time period setup for AGS (Batch3) development. Fourth, the result proved that the stability and ability of AGS (Batch4) were to be reformed after long term storing and under a fluctuated OLR and a low COD/N ratio. Fifth, the biokinetics parameters attained during the steady state further proved the result and the conclusion given from the first result until the fourth result. Thus, the present thesis is enlightened and being overcome with a much promising new insight in AGS formation and stability by preparing the development medium of AGS similar to real site. Research results also help to enlighten the limitations experienced by AGS technology and further endorsed for the full-scale application.